IDENTIFICATION OF GRAM-POSITIVE BACTERIA AND THEIR VIRULENCE CHARACTERISTICS FROM PIG TONSIL ISOLATES BASED ON CATALASE TEST AND HEMOLYTIC PROPERTIES - Pamungkas, Kivlan Satrio; Suardana, I Wayan; Adnyana, Ida Bagus Windia (Buletin Veteriner Udayana, 2025)
Tonsils are an entry and growth site for microbial colonisation and pathogenic bacteria. The tonsils of pig harbour both Gram-positive and Gram-negative bacteria. Some Gram-positive bacteria, such as Staphylococcus, Enterococcus, lactobacillus and Streptococcus can threaten pig productivity. Therefore, this study aimed to identify Gram-positive bacterial species isolated from pig tonsils using the catalase test and to determine their virulence characteristics based on hemolysis types on blood agar. A total of 74 presumptive Gram-positive isolates preserved in 30% glycerol were cultured and tested using Gram staining, catalase tests, and hemolysis assays. The results indicated that all isolates were Gram-positive, with 56.7% identified as Staphylococcus (catalase-positive) and 43.3% as Streptococcus (catalase-negative). Hemolysis tests showed that 43.2% of the isolates were alpha-hemolytic, 41.8% beta-hemolytic, and 15% gamma-hemolytic. Beta hemolysis is associated with high virulence, while alpha and gamma hemolysis are generally linked to opportunistic or non-pathogenic bacteria. This study provides preliminary insights into the identification of potential pathogenic bacteria in pig tonsils and their virulence characteristics based on hemolysis types.